Conjugate effects of temperature sensitive viscosity and thermal conductivity on free convection flow along a wavy surface with heat generation - Alim, Md. Abdul; Akand, M. Miraj; Karim, M. Rezaul (Journal of Naval Architecture and Marine Engineering, 2013)
The effects of internal heat generation on natural convection flow with temperature dependent variable viscosity along a uniformly heated vertical wavy surface have been investigated. The governing boundary layer equations are first transformed into a non-dimensional form using suitable set of dimensionless variables. The resulting nonlinear system of partial differential equations are mapped into the domain of a vertical flat plate and then solved numerically employing the implicit finite difference method, known as Keller-box scheme. Numerical results of the surface shear stress in terms of skin friction coefficient and the rate of heat transfer in terms of local Nusselt number, the stream lines as well as the isotherms are shown graphically for a selection of parameters set consisting of viscosity variation parameter e, thermal conductivity parameter g, heat generation parameter Q and Prandtl number Pr. Numerical results of the local skin friction coefficient and the rate of heat transfer for different values are presented in tabular form and graphically. DOI: http://dx.doi.org/10.3329/jname.v10i2.9450